Clinical Case 21—An unusual cause for hypoxemia and breathlessness. (21st October 2022) - de Figueiredo, Margarida Gancho; Paula, Sofia; Almeida, Samuel; Gomes, Francisco; Ferreira, Filipa; Luz, João; Cunha, Diogo; Baltazar, Oliveira; Almeida, Lurdes
Abstract: 75-year-old woman with past medical history of ischemic stroke in 2019, when complementary diagnostic tests were performed and it was found that the patient had a patent foramen ovale (PFO). Current hospitalization due to COVID-19 pneumonia, which was complicated by bacterial co-infection and intermediate-low risk right main pulmonary artery thromboembolism. The patient was successfully treated, with improvement of the clinical condition and evident imaging resolution of pulmonary cavitations and recanalization of the right pulmonary artery. However, something intriguing was observed: the patient presented dyspnea in the upright position and a decline in transcutaneous oxygen saturation from 96% in the supine position to 85% in orthostatism, with reversal of these findings with the recumbency. This led to the suspicion of platypnea-orthodeoxia syndrome. A transesophageal echocardiogram with bubble test was then performed, revealing an atrial shunt in the supine position without Valsalva maneuver. With these evidences, the diagnosis of platypnea-orthodeoxia syndrome was made. Even though the patient was >60 years, due to important right-to-left shunt, the history of stroke and the current platypnea-orthodeoxia, it was decided to close the PFO. The day after the procedure, the patient was placed in the upright position, maintaining an oxygen saturation of 96%. This case is an example that the decision of closing PFO must be individualized, not focusing only on patient's age, but also on his medical history and current situation, as indicated in the 2022 Guidelines for the Management of Patent Foramen Ovale. Figure 1 Transesophageal echocardiogram showing interatrial communication.